Impact Of The Terms-Of-Trade On Business Cycles In Slovak And Czech Economies - Karol Szomolanyi; Martin Lukacik; Adriana Lukacikova (European Scientific Journal, ESJ, 2016)
Using Slovak and Czech data and the empirical structural vector autoregressive model, the observed impact of the terms-of-trade on business cycles is very small. Furthermore we observe Obstfeld-Svensson-Razin effect of terms-of-trade in both countries. The trade balance negatively reacts on the changes in terms-of-trade. However the theoretical model with import-able, export-able and non-tradable goods calibrated with the empirical observations in Slovakia and Czech Republic does not suit to the empirical model. The reactions of consumption, output and real exchange rate on the terms-of-trade shocks are overestimated and the trade balance reacts positively on the terms-of-trade shocks in the theoretical models for both countries. Moreover, the theoretical model calibrated using Slovak and Czech data predicts Harberger-Laursen-Metzler effect. The trade balance positively reacts on the changes in terms-of-trade. The theoretical and empirical mismatch in literature dealing with the terms of trade influence is confirmed. The paper is divided into two parts. Firstly, structural vector autoregressive model is introduced and estimated. Secondly, the theoretical model with import-able, export-able and non-tradable goods is presented and calibrated. Data of Slovak and Czech economy are used.